PENGARUH LINGKUNGAN DAN KOMUNIKASI TERHADAP KEPUASAN KERJA PEGAWAI DINAS PANGAN KABUPATEN BOALEMO - Ermin Manggena; Darman; Maman Musa (Journal of Economic, Business, and Administration (JEBA), 2023)
This study aims to determine: (1) The Effect of the Work Environment on Job Satisfaction of Employees of the Food Service of Boalemo Regency, (2) The Effect of Communication on Job Satisfaction of Employees of the Food Service of Boalemo Regency, (3) The Effect of Work Environment and Communication on Job Satisfaction of Employees of the District Food Service Boalemo. The research method used is a quantitative associative research approach which intends to understand the phenomenon of what is experienced holistically, and by means of descriptions in the form of words and language, in a specific context to provide solutions or input for problems that are appropriate and related to the problem. The results of the research study are: (1) partially the work environment has an influence on employee job satisfaction at the Boalemo District Food Service, (2) partially communication has an influence on employee job satisfaction at the Boalemo District Food Service and (3) Simultaneously the environment work and communication have an influence on employee job satisfaction at the Boalemo District Food Service.